Preparation, characterization, and process performance of composite fibrous adsorbents as cation exchangers for high throughput and high capacity bioseparations - Gavara, Poondi Rajesh (2012)
Fibrous materials are proposed as novel chromatographic supports depicting high throughput and high product capacity. In this work, a composite fiber harboring strong cation-exchange moieties has been investigated. Such materials were characterized by a plethora of physical methods including degree of swelling (DS), scanning electron microscope (SEM), confocal laser scanning microscopy (CLSM), and Fourier transform infrared spectroscopy-attenuated total reflection (FTIR-ATR). The composite showed a high degree of grafting (∼30%) and exhibited a high swelling ratio (∼300%). Moreover, homogenous grafting and the development of an internal (functional) hydrogel were observed. The fibrous adsorbent was packed utilizing a designed " double roll" supported-structure and subsequently tested for packing efficiency and chromatography performance. The mentioned system showed similar packing efficiency of height equivalent to a theoretical plate (HETP) value and higher permeability coefficient (0.92×10 -7cm 2) than commercial resins. Experimentally determined Peclet number (Pe) values were within the range 60-90, suggesting a close-to-plug-flow condition. Total ionic capacity of the fibrous adsorbent was determined by the transition pH method. A capacity of 6.5mequiv./g was obtained. Moreover, a high dynamic binding capacity for lysozyme was found to be 283mg/g. On the other hand, a bed of randomly packed fiber also demonstrated high-resolution ability when a mixture of model protein was utilized to that end. Resolution was maintained at high flow rates (up to 900cm/h) and utilizing shorter gradient development routines. Direct sequestration of a model protein (lysozyme) was also possible from an artificial mixture containing 1.5% yeast homogenate. Summarizing, the composite fibrous adsorbents exhibited superior performance during early protein capture and intermediate-resolution applications.